PTFEP–Al2O3 hybrid nanowires reducing thrombosis and biofouling. Issue 12 (11th November 2019) - Haidar, Ayman; Ali, Awadelkareem A.; Veziroglu, Salih; Fiutowski, Jacek; Eichler, Hermann; Müller, Isabelle; Kiefer, Karin; Faupel, Franz; Bischoff, Markus; Veith, Michael; Aktas, Oral Cenk; Abdul-Khaliq, Hashim
Abstract : Superhydrophobic PTFEP modified Al2 O3 nanowires (NWs) reduce both platelet adhesion/activation and bacterial adherence/colonization. Abstract : Thrombosis and bacterial infection are major problems in cardiovascular implants. Here we demonstrated that a superhydrophobic surface composed of poly(bis(2, 2, 2-trifluoroethoxy)phosphazene) (PTFEP)–Al2 O3 hybrid nanowires (NWs) is effective to reduce both platelet adhesion/activation and bacterial adherence/colonization. The proposed approach allows surface modification of cardiovascular implants which have 3D complex geometries.